The Concept and Relevance of Sacred Hospitality in the Abrahamic Tradition for Global Peace - Rahmawati, Indah; Miharja, Deni (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This research is motivated by the limitations of the concept of tolerance in building genuine interfaith relationships. Spiritually and empathetically, tolerance is more passive than active involvement. Because tolerance is often limited to the acceptance of differences. The concept of sacred hospitality in the Abrahamic traditions (Islam, Christianity, Judaism) can serve as a new mindset for creating world peace through interfaith spirituality. This study aims to analyze the concept of sacred hospitality in the three Abrahamic traditions, determine the moral and theological values contained therein, and interpret their relationship to strengthen the ethics of peace between religious communities and universal humanity. This study uses a library research approach with a qualitative descriptive method. Primary data were collected from the Tanakh, the Bible, and the Qur'an, while secondary data were collected from literature related to theology, philosophy, and interfaith studies. The study found that sacred hospitality includes unconditional love, recognition of differences, and self-transforming openness. The concept of hospitality, in this case, goes beyond simply accepting differences, as it provides for active spiritual engagement, balanced dialogue, and recognition of inherent human dignity. It is crucial to incorporate the values of sacred hospitality into interfaith education, interfaith dialogue, and social policies as a concrete step toward creating world peace grounded in spirituality and holistic humanity.